Multiplex micro‐respiratory measurements of Arabidopsis tissues. Issue 3 (8th July 2013) - Sew, Yun Shin; Ströher, Elke; Holzmann, Cristián; Huang, Shaobai; Taylor, Nicolas L.; Jordana, Xavier; Millar, A. Harvey
Summary Researchers often want to study the respiratory properties of individual parts of plants in response to a range of treatments. Arabidopsis is an obvious model for this work; however, because of its size, it represents a challenge for gas exchange measurements of respiration. The combination of micro‐respiratory technologies with multiplex assays has the potential to bridge this gap, and make measurements possible in this model plant species. We show the adaptation of the commercial technology used for mammalian cell respiration analysis to study three critical tissues of interest: leaf sections, root tips and seeds. The measurement of respiration in single leaf discs has allowed the age dependence of the respiration rate in Arabidopsis leaves across the rosette to be observed. The oxygen consumption of single root tips from plate‐grown seedlings shows the enhanced respiration of root tips and their time‐dependent susceptibility to salinity. The monitoring of single Arabidopsis seeds shows the kinetics of respiration over 48 h post‐imbibition, and the effect of the phytohormones gibberellic acid (GA3) and abscisic acid (ABA) on respiration during seed germination. These studies highlight the potential for multiplexed micro‐respiratory assays to study oxygen consumption in Arabidopsis tissues, and open up new possibilities to screen and study mutants and to identify differences in ecotypes or populations of different plant species.